Accurate and Reproducible Application of the RECIST Criteria in CT Reporting in Oncology: A Learning Module - Nancy McNulty; Petra Lewis (Association of American Medical Colleges, 2010)
Abstract Introduction The response evaluation criteria in solid tumors (RECIST) criteria were first published in 2000, and updated in 2009. Several important changes were made in the updated version (version 1.1) which significantly impact the appropriate selection of target lesions and the methods in which they are measured. It is difficult to find the time to educate department faculty and trainees on these changes, yet it is of the utmost importance to ensure accurate reporting. This educational module is designed for faculty, fellows, and residents who interpret and report cross sectional imaging studies on oncology patients. Methods This resource contains a PowerPoint file which can be used in three ways. First, it can be presented orally at an educational conference to an entire department or section familiar with these studies. Second, it can be viewed as a self-paced learning module which would optimally be completed in one session. The third use is as a quick-reference resource at the picture archiving and communication system workstation. The presentation can be loaded onto the computer at workstations where cross sectional imaging studies are read, to be used as a quick reference. The final slide in the presentation is a primer, used to guide appropriate selection of target lesions. This slide contains hyperlinks to other points in the presentation, to allow for a quick and targeted review of certain pertinent topics. Results This learning module has been used as both an oral presentation and a self-paced learning module. The presentation was given to radiology residents during noon conference and was well received. This module was also emailed out to all faculty, fellows, and residents for self-study. In addition, the module has been placed on the desktop at all computers where CT scans are interpreted at the authors' institution, to be used as a quick reference. Discussion The versatility of this resource allows the user several options to educate faculty and trainees on the proper application of the RECIST criteria. Accurate reporting using these criteria is essential to guide the proper care and treatment course of oncology patients. These criteria are also widely used in research trials, where accurate reporting is crucial.